Cell penetrating peptide-modified nanoparticles for tumor targeted imaging and synergistic effect of sonodynamic/HIFU therapy - Li Y; Hao L; Liu F; Yin L; Yan S; Zhao H; Ding X; Guo Y; Cao Y; Li P; Wang Z; Ran H; et al. (International Journal of Nanomedicine, 2019)
Yizhen Li,1–3,* Lan Hao,1,2,* Fengqiu Liu,1,2 Lixue Yin,3 Sijing Yan,4 Hongyun Zhao,1,2,5 Xiaoya Ding,6 Yuan Guo,1,2 Yang Cao,1,2 Pan Li,1,2 Zhigang Wang,1,2 Haitao Ran,1,2 Yang Sun1,21Institute of Ultrasound Imaging & Department of Ultrasound, The Second Affiliated Hospital of Chongqing Medical University, 400010 Chongqing, People’s Republic of China; 2Chongqing Key Laboratory of Ultrasound Molecular Imaging, 400010 Chongqing, People’s Republic of China; 3Department of Cardiovascular Ultrasound and Non-invasive Cardiology, Sichuan Academy of Medical Science & Sichuan Provincial People’s Hospital, Chengdu, Sichuan Province, 610072, People’s Republic of China; 4Chongqing Hospital of Traditional Chinese Medicine, Chongqing 400021, People’s Republic of China; 5Department of Gastroenterology, The Second Hospital Affiliated to Chongqing Medical University, Chongqing, 400010, People’s Republic of China; 6Department of Ultrasound, University-Town Hospital of Chongqing Medical University, Chongqing, 401331, People’s Republic of China*These authors contributed equally to this workBackground: Theranostics based on multifunctional nanoparticles (NPs) is a promising field that combines therapeutic and diagnostic functionalities into a single nanoparticle system. However, the major challenges that lie ahead are how to achieve accurate early diagnosis and how to develop efficient and noninvasive treatment. Sonodynamic therapy (SDT) utilizing ultrasound combined with a sonosensitizer represents a novel noninvasive modality for cancer therapy. Different ultrasound frequencies have been used for SDT, nevertheless, whether the effect of SDT can enhance synergistic HIFU ablation remains to be investigated.Materials and methods: We prepared a nanosystem for codelivery of a sonosensitizer (methylene blue, MB) and a magnetic resonance contrast agent (gadodiamide, Gd-DTPA-BMA) based on hydrophilic biodegradable polymeric NPs composed of poly (lactic-co-glycolic acid) (PLGA). To enhance accumulation and penetration of the NPs at the tumor site, the surface of PLGA NPs was decorated with a tumor-homing and penetrating peptide-F3 and polyethylene glycol (PEG). The physicochemical, imaging and therapeutic properties of F3-PLGA@MB/Gd and drug safety were thoroughly evaluated both in vitro and in vivo. F3-PLGA@MB/Gd was evaluated by both photoacoustic and resonance imaging.Results: F3-PLGA@MB/Gd NPs exhibited higher cellular association than non-targeted NPs and showed a more preferential enrichment at the tumor site. Furthermore, with good drug safety, the apoptosis triggered by ultrasound in the F3-PLGA@MB/Gd group was greater than that in the contrast group.Conclusion: F3-PLGA@MB/Gd can work as a highly efficient theranostic agent, and the incorporation of targeted multimodal and combined therapy could be an encouraging strategy for cancer treatment.Keywords: cell penetrating peptide, tumor targeted, image, sonodynamic, HIFU, nanoparticle